Prophets of computing : visions of society transformed by computing - Lente, Dick van (Association for Computing Machinery;, 2022)
When electronic digital computers first appeared after World War II, they appeared as a revolutionary force. Business management, the world of work, administrative life, the nation state, and soon enough everyday life were expected to change dramatically with these machines' use. Ever since, diverse prophecies of computing have continually emerged, through to the present day. As computing spread beyond the US and UK, such prophecies emerged from strikingly different economic, political, and cultural conditions. This volume explores how these expectations differed, assesses unexpected commonalities, and suggests ways to understand the divergences and convergences. This book examines thirteen countries, based on source material in ten different languages--the effort of an international team of scholars. In addition to analyses of debates, political changes, and popular speculations, we also show a wide range of pictorial representations of "the future with computers."
Keywords: Computers -- Social aspects.; Computers -- History.; elektronické knihy; electronic books